在数列 {an} 与 {bn} 中,数列 {an} 的前n项和Sn满足 Sn=n2+2n,数列 {bn} 的前n项和Tn满足 3Tn=nbn+1,且b1=1,n∈N*. (Ⅰ)求数列 {an} 的通项公式; (Ⅱ)求数列 {bn} 的通项公式; (Ⅲ)设 cn=
|
(Ⅰ)∵Sn=n2+2n,…①
∴Sn-1=(n-1)2+2(n-1),n≥2. …②
①-②得 an=2n+1,n≥2. …2分
∵a1=S1=3 满足上式,
∴an=2n+1,n∈N*. …4分
(Ⅱ)∵3Tn=nbn+1,…③
∴3Tn-1=(n-1)bn,n≥2. …④
③-④得 3bn=nbn+1-(n-1)bn,即
=bn+1 bn
,n≥2. …5分n+2 n
∴
=b3 b2
,4 2
=b4 b3
,5 3
=b5 b4
,…,6 4
=bn bn-1
.n+1 n-1
将以上各式连乘得
=bn b2
,n≥2. …7分n(n+1) 6
∵b1=1,∴b2=3.
∴bn=
,n≥2. …8分n(n+1) 2
∵b1=1满足上式,
∴bn=
,n∈N*. …9分n(n+1) 2
(Ⅲ)由(Ⅰ)(Ⅱ)得 cn=n2cos
,…10分2nπ 3
(1)当 n=3k (k∈N*)时,
Rn=(c1+c2+c3)+(c4+c5+c6)+…+(c3k-2+c3k-1+c3k)
=(-
-12 2
+32)+(-22 2
-42 2
+62)+…+[-52 2
-(3k-2)2 2
+(3k)2](3k-1)2 2
=
+13 2
+…+31 2
=18k-5 2
=9k2+4k 2
.3n2+4n 6
(2)当 n=3k-1(k∈N*)时,
Rn=
-c3k=9k2+4k 2
=-9k2+4k 2
.-3n2-2n+1 6
(3)当 n=3k-2(k∈N*)时,
Rn=
-c3k-1=-9k2+4k 2
=-2k+1 2
.-2n-1 6
综上,Rn=
(k∈N*) …14分.
,n=3k3n2+4n 6
,n=3k-1-3n2-2n+1 6
,n=3k-2-2n-1 6